HUBUNGAN ANTARA PARTISIPASI PENYUSUNAN ANGGARAN DAN MANAGERIAL PERFORMANCE : MOTIVASI, DESENTRALISASI DAN STYLE LEADERSHIP SEBAGAI VARIABEL MODERATING - Al, Muhammad Al (Jurnal Analisis Bisnis Ekonomi, 2004)
The relationship between budget participation and managerial performance has been attracting research' attentions. However, the result of previous studies on the relationship between budget participation and managerial performance have been inconclusive and often contadictionary. The study empirically examined the effect of budget participation on managerial performance using a contingency approach. Three contigent variabels were investigated, motivation, decentralization and style leadership. The result indicated that the ineraction between budget participation and managerial performance did nor direct effect. But motivation and decentralization was found to have a significant effect on the relationship between budget participation and managerial performance. And style was not found to have a significant.